Antioxidant activity improvement of soybean meal by microbial fermentation - Pairote Wongputtisin (2018)
The improvement of antioxidant activity of soybean meal (SBM), an important protein source for monogastric animals, was studied by solid state fermentation. Fermented soybean meal (FSBM) was produced using pure culture of each Bacillus subtilis strain MR10 and TK8, B. natto and Rhizopus oligosporus that are accepted as GRAS microorganisms. It was found that the antioxidant activity in term of scavenging effect and reducing power was increased significantly at p<0.05. FSBM produced by Bacillus sp. and R. oligosporus showed percentage scavenging activity at the level of 70-99 and 49%, respectively, while only 25% of scavenging activity was found in SBM. Furthermore, the reducing power value (A 700) of every FSBM and SBM was between 0.827-1.031 and 0.299, respectively. © 2007 Academic Journals.